Drugs: Their Use And The Reasons For Their Spread In Society - Ahmed Meri , Marwa; Hamid Al-Hakeem, Aaya; Saad Al-Abeadi , Rukaya (Medical Science Journal for Advance Research, 2022)
Background : This study aimed to identify the types of drugs and the factors related to drug abuse and addiction, and to reveal the reasons for the spread of drug abuse and addiction among young people, and to determine the effects of drug abuse and addiction among young people in all aspects of life, and to clarify the extent of the impact of drugs on the individual and on various aspects of his life. The study came to a number of conclusions, the most significant of which are: Narcotics are present and they are major drugs, including opium and its derivatives, cocaine, khat, heroin, and amphetamines; people turn to narcotic substances to relieve some of their symptoms; and people continue using those substances even after their illness has passed, they believe. It is said that this substance is able to make him in a good health condition, while some resort to taking drugs in order to feel happiness and escape from the burdens and problems of life; And the presence of many negative effects due to drug abuse and addiction, and the presence of an active and influential role of great importance for the family, their educational institutions, and the media in terms of protecting children and students from drug abuse.